2014
DOI: 10.2147/ijwh.s59852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hormonal contraceptives on lipid profile and the risk indices for cardiovascular disease in a Ghanaian community

Abstract: BackgroundHormonal contraceptives (HCs) have been shown to alter lipid profile among various population groups with different patterns of dyslipidemia and cardiovascular (CV) risk. The study aimed at determining the lipid profile pattern and CV risk in a Ghanaian cohort.MethodsPurposive random sampling was done. Forty-seven and 19 cases were on oral contraceptives (OCs) and injectable contraceptives (ICs), respectively; five were on subdermal implant. Twenty-four non-users served as controls. Biodemographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
49
4
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 27 publications
10
49
4
13
Order By: Relevance
“…Therefore it has been concluded that OCs increase the level of high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), total cholesterol (TC) and triglycerides (TG). Asare et al (2014) have reported that total cholesterol and low density lipoprotein were significantly different in the oral contraceptive using group compared to the control group which is consistent with the present study. The higher results are obtained as a result of oral contraceptives use.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore it has been concluded that OCs increase the level of high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), total cholesterol (TC) and triglycerides (TG). Asare et al (2014) have reported that total cholesterol and low density lipoprotein were significantly different in the oral contraceptive using group compared to the control group which is consistent with the present study. The higher results are obtained as a result of oral contraceptives use.…”
Section: Discussionsupporting
confidence: 93%
“…According to the TAG/HDL-C and LDL-C/HDL-C ratios of the present study, adjustments of SLP patterns in the fibrotic rats, irrespective of the type of herbal treatment they received, indicated incidences of atherogenicity as defined elsewhere. 39,58,61,62,63 The massive disarrangement of hepatic tissues architecture of untreated fibrotic rats (Group 3) correlated with the levels of alterations of serum indicators, namely, serum ALT, AST and ALP activities as well as serum TBC as previously described. 12,13,98,99 Additionally, photomicrograph section of hepatic tissues of fibrotic rats ( Figure 6) revealed and confirmed CCl 4 -induced necrosis and steatosis as previously described.…”
Section: Discussionsupporting
confidence: 61%
“…1 Some women complain of weight gain resulting from hormonal contraceptive use and studies done earlier in the Upper West Region of Ghana associated dyslipidemia with prolonged use of these birth control measures. 2 The need to practice family planning cannot be overemphasized and so there is the need to focus on the short to medium term use of contraceptives and cardio vascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular hormonal contraceptives in Ghana are: the OC pills, Implanon NXT, Depo-Medroxyprogesterone acetate, Norigynon, Microgynon, and Microlut, however, the most preferred ones among women attending the family planning clinics in Ghana are: Depo-Provera (depot medroxyprogesterone acetate) (DMPA), an injectable contraceptives (IC) and oral contraceptives (OC). 2 Aside the primary roles of controlling birth, most of these hormonal contraceptives have effects on carbohydrate and lipid catabolism. 4 Some research has reported a 22% rise in Low Density Lipoprotein (LDL) cholesterol among users of combined oral contraceptive (COC) without a concomitant increase in HDL resulting in a reduction of HDL/LDL ratio.…”
Section: Introductionmentioning
confidence: 99%